A phylogenetic analysis of the southern African gecko genus Afroedura Loveridge (Squamata: Gekkonidae), with the description of nine new species from Limpopo and Mpumalanga provinces of South Africa - Jacobsen, Niels H. G.; Kuhn, Arianna L.; Kuhn, Arianna L.; Jackman, Todd R.; Bauer, Aaron M. (Zootaxa, 2014)
A molecular phylogeny of the largely rupicolous geckos of the gekkonid genus Afroedura is presented based on a combination of mitochondrial and nuclear gene sequence data. Previously recognized species groups are only partly recovered, with A. pondolia retrieved as very distantly related to the congeners to which it was previously considered allied. Afroedura hawequensis forms a monotypic group that is sister to all other species, which are allocated to the A. nivaria, A. transvaalica, A. africana, A. multiporis, A. marleyi, and A. langi groups. The taxonomic status of species occurring in the former Transvaal province of South Africa (now Limpopo and Mpumalanga provinces) is reviewed based on morphological and molecular evidence. Afroedura rupestris sp. nov. is described in the A. multiporis group, A. maripi sp. nov., A. pongola sp. nov., and A. rondavelica sp. nov., are described in the A. marleyi group, and A. broadleyi sp. nov., A. granitica sp. nov., A. leoloensis sp. nov., A. pienaari sp. nov., and A. waterbergensis sp. nov. are described in the A. langi group. In addition, A. haackei, A. namaquensis, and A. tirasensis, are all raised to specific status. The description of nine new species highlights Limpopo and Mpumalanga provinces as previously unrecognized centers of diversity for the genus Afroedura. A key to the species of Afroedura is provided.